Short-term effects of opioids during therapeutic hypothermia for neonatal encephalopathy - Jumani, Tina; Mishra, Priya; Robinson, Tonya; Shenberger, Jeffrey S.; Davis, Jonathan M.; Sweigart, Benjamin; Turcu, Rodica M. (Frontiers in Pediatrics, 2024)
Objective: To examine the effects of opioids during therapeutic hypothermia (TH) on short-term outcomes in neonates with neonatal encephalopathy (NE).Methods: Multicenter retrospective study of neonates with moderate/severe NE from Jan. 2013-Feb 2021. Opioid exposure was classified as positive (> 0.1 mg/kg) or negative (no exposure or <0.1 mg/kg) based on cumulative morphine milligram equivalents (MME). Negative binomial regression models were used to evaluate clinical outcomes.Results: One hundred and twenty neonates were included. Adjusted analyses indicated that opioid exposure was associated with an increase in 1) length of hospitalization, 2) hypotension/use of vasopressors, and 3) need for and longer duration of mechanical ventilation.Many findings persisted even after adjusting for site and the presence of confirmed seizures (a marker of disease severity).Discussion: Opioid use during TH was associated with adverse effects on short-term outcomes.Caution should be exercised when using opioids during TH until longer-term neurodevelopmental outcome studies can be conducted in larger cohorts.